2018
DOI: 10.5935/0103-507x.20180062
|View full text |Cite
|
Sign up to set email alerts
|

suPAR in the assessment of post intensive care unit prognosis: a pilot study

Abstract: ObjectiveTo determine the performance of soluble urokinase-type plasminogen activator receptor upon intensive care unit discharge to predict post intensive care unit mortality.MethodsA prospective observational cohort study was conducted during a 24-month period in an 8-bed polyvalent intensive care unit. APACHE II, SOFA, C-reactive protein, white cell count and soluble urokinase-type plasminogen activator receptor on the day of intensive care unit discharge were collected from patients who survived intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Su-PAR and PAI-1 concentrations were higher in critically ill patients compared to healthy volunteers. Another study by Silvestre et al, 20 found that, SOFA was independently associated with a higher risk of in-hospital mortality, 28day mortality and 90-day mortality.…”
Section: Discussionmentioning
confidence: 92%
“…Su-PAR and PAI-1 concentrations were higher in critically ill patients compared to healthy volunteers. Another study by Silvestre et al, 20 found that, SOFA was independently associated with a higher risk of in-hospital mortality, 28day mortality and 90-day mortality.…”
Section: Discussionmentioning
confidence: 92%
“…As the urokinase receptor system regulates the confluence of inflammatory, immune, coagulation, and fibrinolytic responses, suPAR has been used in the diagnosis and prognosis of multiple inflammatory, infectious, autoimmune, neoplastic conditions, as well as coronary heart disease and heart failure. [1][2][3][4][5][6][7][8][9][10] Regardless of the underlying pathology, serum levels are raised in acutely ill patients, and also have a prognostic value as they predict high mortality. 6 As the biochemical and molecular mechanisms underpinning these properties remain unclear, suPAR is currently considered a non-specific biomarker for disease presence, progression, and severity.…”
Section: Introductionmentioning
confidence: 99%